2006
DOI: 10.2486/indhealth.44.613
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Status of Municipal Solid Waste Incinerator Workers Compared with Local Government Office Workers

Abstract: Recently in Japan dioxin problem of municipal solid waste incinerator (MSWI) became social issue. The news spread all around Japan and induced fear that workers at incinerators would suffer from cancer or other serious illness induced by the exposure to dioxins. Authors were interested in the effect of this stressful event occurred to the workers and intended to evaluate mental health status of MSWI workers compared with office workers. Subjects were male workers from two MSWI plants and a local government off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
(5 reference statements)
1
6
0
Order By: Relevance
“…The higher prevalence of mental disorders in the Japanese study might be attributable to the study participants’ occupation. Incinerator workers were aware and afraid of their occupational exposure to extremely hazardous agents such as dioxin which are released during the incineration process [ 13 ]. This knowledge elevated self-perceived mental distress among Japanese MSW workers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The higher prevalence of mental disorders in the Japanese study might be attributable to the study participants’ occupation. Incinerator workers were aware and afraid of their occupational exposure to extremely hazardous agents such as dioxin which are released during the incineration process [ 13 ]. This knowledge elevated self-perceived mental distress among Japanese MSW workers.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mean score (standard deviation) of DASS-S among WCs in this study was moderate (9.7 ± 7.8), 4.1% and 3.1% of WCs showed moderate to severe levels of stress symptoms, respectively. Research on psychological stress among WCs has thus far been limited [4,[10][11][12][13]. Among them, only one study reported the prevalence of anxiety and depression among Japanese MSW incinerator workers, using the Japanese version of the Profile of Mood States Test [13].…”
Section: Prevalence Of Psychological Stress Among Waste Collectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one study investigated stress levels secondary to the fear of occupational exposure to dioxins among municipal solid waste incinerator workers, which was lower than the general stress experienced by office workers 87 …”
Section: Resultsmentioning
confidence: 99%